Training cognition : optimizing efficiency, durability, and generalizability - Healy, Alice F.; Bourne, Lyle Eugene, 1932- (New York, NY : Psychology Press, 2012)
"This book describes research on training using cognitive psychology to build a complete empirical and theoretical picture of the training process. It includes a review of relevant cognitive psychological literature, a summary of recent laboratory experiments, a presentation of original theoretical ideas, and a discussion of possible applications to real-world training settings"--Provided by publisher.
(from the cover) Training is both a teaching and a learning experience, and just about everyone has had that experience. Training involves acquiring knowledge and skills. This newly acquired training information is meant to be applicable to specific activities, tasks, and jobs. In modern times, where jobs are increasingly more complex, training workers to perform successfully is of more importance than ever. The range of contexts in which training is required includes industrial, corporate, military, artistic, and sporting, at all levels from assembly line to executive function. The required training can take place in a variety of ways and settings, including the classroom, the laboratory, the studio, the playing field, and the work environment itself. The general goal of this book is to describe the current state of research on training using cognitive psychology to build a complete empirical and theoretical picture of the training process. The book focuses on training cognition, as opposed to physical or fitness training. It attempts to show how to optimize training efficiency, durability, and generalizability The book includes a review of relevant cognitive psychological literature, a summary of recent laboratory experiments. a presentation of original theoretical ideas, and a discussion of possible applications to real-world training settings.
Introduction : Training MURI project / Alice F. Healy and Lyle E. Bourne Jr. -- Empirically valid principles of training / Alice F. Healy, Vivian I. Schneider, and Lyle E. Bourne Jr. -- Basic research on training principles / Alice F. Healy, Lyle E. Bourne Jr., and other members of the Healy-Bourne laboratory -- Role of attention in training / Christopher D. Wickens -- Training and transfer of basic components of skill / Robert W. Proctor, Motonori Yamaguchi, and James Miles -- Automation and effective training / Benjamin Clegg and Eric Heggestad -- Impact of Technology on Training / Stephen Goldberg and Paula Durlach -- Training Taxonomy : Tasks, methods, and performance measures / William D. Raymond, Alice F. Healy, and Lyle E. Bourne Jr. -- Instance-based models of training / Cleotilde Gonzalez -- Component-process models of training / Carolyn J. Buck-Gengler -- Training models : Comparison, evaluation, and optimization / Bengt Fornberg and William D. Raymond -- Over-arching quantitative framework of training / Matt Jones ... [et al.] -- Principles applicable to education and training / Mark A. McDaniel -- Training for the real world / Immanuel Barshi, Loukia Loukopoulos, and Key Dismukes -- Conclusions : Current status of knowledge about training / Lyle E. Bourne Jr. & Alice F. Healy.
Keywords: Cognitive styles; Employees -- Training of; Cognitive Science -- education; Cognitive Science -- methods; Cognition; Models, Educational; Task Performance and Analysis; kognitivni trening; kognitivni stilovi; trening zaposlenika; kognitivna psihologija